Prinsip Kerahasiaan dan Prinsip Kehati-Hatian dalam Perlindungan Data Nasabah Bank Syariah - Farrun, Ravena ida; Purwanto, Aldira Mara Ditta Caesar (Universitas Batanghari Jambi, 2024)
Islamic banks conduct their business activities in accordance with the provisions of the Sharia Banking Law, adhering to the principles of confidentiality and prudence, which are fundamental to gaining customer trust. The business activities of Islamic banks involve the collection of funds (funding) and financing (lending) based on customer trust. In addition to trusting the bank with their funds, customers also trust the bank with their sensitive personal data, which must be protected as bank confidentiality according to Article 41 of the Sharia Banking Law. This study employs a normative juridical method to examine the principles of confidentiality and prudence in the business activities of Islamic banks in protecting personal data. The study utilizes primary and secondary legal materials, reviewing literature from previous research and conducting interviews. The research findings indicate that a data breach caused by a ransomware attack experienced by BSI threatens the bank's reputation. BSI must implement data protection measures to restore customer trust through confidentiality agreements. BSI also standardizes all banking systems used. Customers affected by data breaches can file complaints with BSI and the Financial Services Authority (OJK) as the supervisory body, and the bank must protect customers as stipulated by the regulations.